Establishing a standardized system for review and adjudication of chronic graft‐vs‐host disease data in accordance with the National Institutes Consensus criteria. Issue 4 (26th June 2019) - Dierov, Djamilia; Webb, Nicholas; Fatmi, Samira; Nwanne, Chamberlain; Ciolino, Cristi; Mosesso, Kara; Nieves, Jimmy; Perales, Miguel‐Angel; Prockop, Susan E.; Ponce, Doris M.
Abstract: Graft‐vs‐host Disease (GVHD) is a frequent complication following allogeneic stem cell transplantation (allo‐HCT). The National Institute of Health consensus group established new guidelines for the evaluation of chronic GVHD. However, GVHD assessment remains challenging due to its complexity and requirement for laborious evaluation. We, therefore, established a standardized approach for the assessment of chronic GVHD in accordance with the NIH consensus criteria (NCC) guidelines. At a single institution, all allograft recipients were evaluated for GVHD within the first‐year post allo‐HCT following a three‐step workflow (real‐time assessment, consensus review, and documentation). A GVHD adjudication committee was created and a dynamic electronic GVHD data capture form was developed guiding the clinician through a comprehensive review of systems following the NCC guidelines. We found that the assessment and reporting of GVHD reached 100% compliance. The establishment of an institutional GVHD adjudication committee enabled standardized assessment of GVHD. Our workflow can be adopted by other centers to create a similar framework for dedicated GVHD evaluation.